The influence of knee joint angle and time of force application on vertical jump height during volleyball commit-block - Riva, G.; Rossi, A.; Bonfanti, L.; Formenti, D.; Alberti, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Blocking successfully is a crucial feature of winning in volleyball. Key points for the effectiveness of block are anticipation, decision-making, movement speed and jumping ability (Lobietti, 2009). It was found that jumping from a position with knees more flexed seems to be the best strategy to achieve the best performance (Gheller et al., 2015). However, during volleyball commit-block (VCB) the time spent during deeper squat could negatively affect the efficacy of the VCB (Ficklin et al., 2014). Thus, we aimed to investigate the influence of three different knee starting angles and the time of force application on jumping performance during VCB. Methods: Fifteen volleyball players were recruited (20.27±3.08 yrs, 76.60±9.27 kg, 184.53±6.63 cm). Players performed three maximal vertical jumps in commit position in front of the volleyball net. In the first one the players performed jumps using their optimal knee joint angle (OR) (105.91±14.80 deg). The second one was performed over their optimal one (OOR) (71.13±18.13 deg) and third one under the optimal one (UOR) (135.94±7.95 deg). The vertical jump height (VJH) and the time of force application (TFA) were obtained by Optojump Next (Microgate, Italy). The knee joint angle (KJA) was assessed using Microsoft Kinect™. One-way MANOVA corrected by GreenHouse-Geisser adjustment was used to detect differences among jumps in VJH, TFA, and KJA. The magnitude of the difference was assessed by partial eta squared (part 2). LSD was performed in accordance to univariate ANOVA. Results: The MANOVA showed statistical difference among the three jumps (F(6,9)=53.273, p<0.001, part 2=0.973). The univariate test detected difference among the independent variable in each dependent variable (VJH: F(1.93,27)=30.601, p<0.001, part 2=0.686; TFA: F(1.96,27.49)=112.196, p<0.001, part 2=0.889; KJA: F(1.807,25.303)=114.864, p<0.001, part 2=0.891). In VJH, difference between OR and UOR (p<0.001) was detected by LSD but no statistical difference was found between OR and OOR (p=0.956). In TFA and KJA, statistical differences were found by LSD in each pairwise comparisons (p<0.001). Discussion: In contrast to Gheller et al. (2015), no difference was found in VJH, even if both TFA and KJA were different between OR and OOR. Thus, jumping at the preferred range should be the best way to reach successful VCB because of higher vertical jump performance applying shorter TFA than OOR.